2020
DOI: 10.1038/s41433-020-01274-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing isolated-check visual evoked potential, pattern visual evoked potential, and standard automated perimetry in dysthyroid optic neuropathy eyes

Abstract: Objective To determine the diagnostic ability of isolated-check visual evoked potential (icVEP), pattern visual evoked potential (pVEP), and standard automated perimetry (SAP) between dysthyroid optic neuropathy (DON) and thyroid-associated ophthalmopathy (TAO) without DON (non-DON). Methods This is a case-control study, 49 bilateral patients (26 DON and 23 non-DON) were included. icVEP, pVEP, and SAP were conducted in all the subjects, icVEP parameters compared were signal-to-noise ratios (SNRs) under 8, 16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…39 However, pVEP (the delayed P100 latent time and/or reduced P100 amplitude) reflects the absolute value of cortical potentials evoked by patterned stimuli, which are prone to fluctuations and are affected by the interference of external noise. 40 Thus, the DTI parameters, which reflect structural integrity, may be associated with, and even show changes prior to, corresponding functional abnormalities of VEPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 However, pVEP (the delayed P100 latent time and/or reduced P100 amplitude) reflects the absolute value of cortical potentials evoked by patterned stimuli, which are prone to fluctuations and are affected by the interference of external noise. 40 Thus, the DTI parameters, which reflect structural integrity, may be associated with, and even show changes prior to, corresponding functional abnormalities of VEPs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the FA and MD of almost all segments of the visual pathway were related to the amplitude and latency of the VEPs, which are signals obtained from electroencephalographic activities 38 that can reflect the functional integrity of the visual pathway 39 . However, pVEP (the delayed P100 latent time and/or reduced P100 amplitude) reflects the absolute value of cortical potentials evoked by patterned stimuli, which are prone to fluctuations and are affected by the interference of external noise 40 . Thus, the DTI parameters, which reflect structural integrity, may be associated with, and even show changes prior to, corresponding functional abnormalities of VEPs.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional PVEP and FVEP can be used for visual function evaluation, which can reflect the light sensitivity of the entire retinal optic nerve, including coarse incoming fibers from the peripheral retinal area and fine incoming fibers from the macula. The application of PVEP and FVEP in various studies, including optic nerve diseases, has been widely reported 14 , 15 . Furthermore, when accompanied by opacities in the ocular media, the role and significance of FVEP in the diagnosis and evaluation of visual function can be further demonstrated 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, isolated-check VEPs (icVEPs), a new visual electrophysiology technology, have been reported to be able to detect glaucomatous visual damage early and quickly [ 7 ]. In recent years, this technique has been applied to detect optic nerve damage of glaucoma [ 8 , 9 , 10 , 11 , 12 , 13 ] and other diseases such as traumatic optic neuropathy [ 14 ] and dysthyroid optic neuropathy [ 15 , 16 ]. The specificity and sensitivity values in detecting glaucomatous optic nerve defects are 84.6–100% and 53.1–83%, respectively [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%